Diabetic Retinopathy in Children with Type I Diabetes Mellitus at A Tertiary Care Center Karachi, Pakistan - Gulab, Shumaila; Khoso, Zubair Ahemd; Ibrahim, Mohsina Noor; Laghari, Taj Muhammad; Ahmed, Syed Habib; Raza, Jamal (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To estimate the frequency of diabetic retinopathy in children with type 1 diabetes mellitus visiting diabetic clinic, National Institute of Child Health, Karachi. Methodology: A retrospective cross sectional study was designed in which 100 children of T1DM were enrolled from Paediatrics endocrinology out-patient department of National Institute of Child Health (NICH) Karachi. Patients between the age of 10-17 years of either gender with duration of T1DM for more than 5 years and no previous known eye or systemic disease other than T1DM were included. The medical records of eye examination of 100 children from January to December 2017 were reviewed and analyzed. Patients were selected through non probability consecutive sampling technique and SPSS version 16 was used to analyze data. Results: One hundred patients of T1DM were enrolled, 82 were male and 18 were females. Mean age of the patients were 11.70±2.38 years (10-17 years) and 59% were <15 years. Mean duration diagnosis of T1DM was 7.05±0.7 years. Mild non proliferative Diabetic retinopathy (NPDR) was found in 17% patients and none had proliferative diabetic retinopathy. Conclusion: Mild Non Proliferative Retinopathy is quite high in our study population which could later on Progresses Proliferative Retinopathy. Screening for all the children should be mandatory for early diagnosis, management and future of eye complications. The screening for eye complications for all children Type I diabetes mellitus should be initiated annually after 5 years of diagnosis and in the children who are 10 years are older. Keywords: Type 1 IDDM, Diabetic Retinopathy (DR), Mild non proliferative diabetic retinopathy (NPDR).